Produktivitas Budidaya Antara Bebek Peking (Anas platyrhynchos) dengan Bebek Hibrida (Anas platyrhynchos domesticus) - Muthmainnah, Atika; Jalali, Khalid (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
Broiler ducks are ducks that are able to grow quickly and can convert feed efficiently into meat with high value. Duck meat has a good structure and structure of the meat. The good structure of duck meat is now popular with the public, because the taste of the meat is delicious and savory. Broiler ducks that are known by the public include hybrid ducks and peking ducks. The demand for duck meat that continues to increase does not change with the availability of duck meat available in the market, to meet the needs of the community. It is possible to breed broiler ducks as proof that the poultry business for ducks is wide open with the promised profit prospects. The purpose of this study was to determine the productivity in broiler duck cultivation which can increase body weight gain quickly, economically and produce meat that has high nutrition to meet public demand. The research method used is literature review by analyzing relevant articles and focusing on the productivity of broiler duck farming. Based on maintenance for 6 weeks, the data obtained was the consumption of hybrid rations as much as 6,514 g/head while in peking ducks as much as 7,601 g/head, PBB in hybrid ducks was 1,237 g/head, while for peking ducks 1,699 g/head, FCR in ducks hybrid 5.29 and peking duck 4.49 and mortality of hybrid duck 4% and peking duck 12%. The weight gain, mortality, and feed conversion of peking ducks were higher than that of hybrid ducks. The conclusion from the results of the study that the best duck genotype to produce FCR was hybrid duck and production performance which included body weight gain, feed consumption and feed conversion in peking ducks and hybrid ducks.